Implementasi Aplikasi Role Sekretaris Di Era Industri 4.0 Dalam Monitoring Rapat Pada PT Langgeng Sejahtera Kreasi Komputasi - Deischa Rizqita Marchellia Rahadian; Agus Garnida; Tengku Sitti Rochmah (Jurnal Sekretaris dan Administrasi Bisnis, 2024)
Technology is developing more rapidly in the industrial era 4.0 marked by the emergence of various sophisticated applications equipped with artificial intelligence to support office work. This has an impact on the work sector that relies on skills, especially the secretarial profession. At the technology company PT Langgeng Sejahtera Kreasi Komputasi, the Redmine project management application has begun to be implemented to run projects within the company. The Redmine is used by the secretary as a meeting monitoring tool. The research method used is descriptive qualitative method with literature study techniques sourced from journals, books, and scientific articles. The results of the study show that Redmine, which is used as a Secretary Role Application to monitor meetings, can produce effective meeting results. However, in practice PT Langgeng Sejahtera Kreasi Komputasi needs to carry out further development.